The global gas transit: new supply chains - S. S. Zhiltsov (Проблемы постсоветского пространства)
The aggravation of relations between Russia and Western countries in early 2022 has marked the formation of new supply chains for energy resources, particularly gas exports. Global energy transit is closely linked to fundamental problems in the world economy, which were aggravated during the coronavirus pandemic. Empirical evidence illustrates that new hydrocarbon supply chains have dramatically changed the balance of power in the global market. The reasons for this were the pricing policy as well as the supply and demand conditions in the market. Considering the gas market as a system of interrelated participants: producers and consumers, the study concludes that energy transit will be determined by the outcome of the economic competition between Russia and the West, as well as the speed of building the infrastructure necessary for the creation and transportation of liquefied natural gas. At the same time, the prospects for low-carbon energy are not so obvious. First of all, the high costs and the unwillingness of many countries to make significant investments hamper a transition. The study concludes that the restructuring of global energy supply chains is in the interests of some developed countries. In general, the current processes in the global energy sector represent a fundamental trend that is associated with the transition period of the world economy. The paper contributes to the knowledge by providing a comprehensive overview of the new processes in the energy sphere.